The language report - Susie Dent (Oxford University Press, 2006)
Backed by the largest language research program in the world at Oxford University Press, this new book presents an up-to-the-minute snapshot of English language today: tracking the latest new words to have entered its usage; investigating old words revived by current events in, for example, the worlds of politics and pop; and examining the most recent trends of language development